2023
DOI: 10.15585/mmwr.su7201a6
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Thoughts and Behaviors Among High School Students — Youth Risk Behavior Survey, United States, 2021

Abstract: Suicide is the third leading cause of death among high school-aged youths aged 14–18 years. The 2021 suicide rate for this age group was 9.0 per 100,000 population. Updating a previous analysis of the Youth Risk Behavior Survey during 2009–2019, this report uses 2019 and 2021 data to examine high school students’ reports of suicidal thoughts and behaviors. Prevalence estimates are reported by grade, race and ethnicity, sexual identity, and sex of sexual contacts. Unadjusted logistic regression models were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…In addition to new questions, prevalence and patterns in health behaviors identified in other reports on longstanding YRBS topics also reinforced the need for specific, tailored public health interventions and resources to improve student health. The report on suicidal thoughts and behaviors indicated an approximately 6 percentage point increase (24% to 30%) from 2019 to 2021 in the prevalence of female students overall who reported seriously considering attempting suicide ( 21 ). From 2019 to 2021, Black, White, and Hispanic female students experienced increases in prevalence of reporting seriously considering attempting suicide ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to new questions, prevalence and patterns in health behaviors identified in other reports on longstanding YRBS topics also reinforced the need for specific, tailored public health interventions and resources to improve student health. The report on suicidal thoughts and behaviors indicated an approximately 6 percentage point increase (24% to 30%) from 2019 to 2021 in the prevalence of female students overall who reported seriously considering attempting suicide ( 21 ). From 2019 to 2021, Black, White, and Hispanic female students experienced increases in prevalence of reporting seriously considering attempting suicide ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The report on suicidal thoughts and behaviors indicated an approximately 6 percentage point increase (24% to 30%) from 2019 to 2021 in the prevalence of female students overall who reported seriously considering attempting suicide ( 21 ). From 2019 to 2021, Black, White, and Hispanic female students experienced increases in prevalence of reporting seriously considering attempting suicide ( 21 ). Other findings indicated a 3.7 percentage point decrease from 2019 to 2021 in the prevalence of HIV testing and a 5 percentage point decrease in the prevalence of testing for sexually transmitted infections among sexually active students ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deaths by suicide have been increasing in youth over the past decade, as have rates of suicide attempt and ideation in this age group (CDC, 2021;Gaylor et al, 2023;Ivey-Stephenson et al, 2019;Ruch et al, 2019;Sheridan et al, 2022). Suicide death rates increase with age throughout adolescence and into young adulthood; rates of death in adolescent males are three times higher than in females (Hughes et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Nationally representative studies of suicidal ideation and attempt have shown increases for adolescents across time (Gaylor et al, 2023;Nock et al, 2013;Twenge et al, 2019). The most recent report from the Youth Risk Behavior Survey (YRBS), a cross-sectional, school-based survey of grades 9-12 conducted biennially, noted that the prevalence of suicidal ideation and behavior in males remained stable across the 2019 and 2021 surveys, with 14.3% reporting they had seriously considered attempting suicide during the past 12 months, 11.6% reporting making a suicide plan, 6.6% reporting attempting suicide, and 1.7% reporting a suicide attempt that required medical attention (Gaylor et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation